Maternal N-Acetylcysteine Therapy Prevents Hypertension in Spontaneously Hypertensive Rat Offspring: Implications of Hydrogen Sulfide-Generating Pathway and Gut Microbiota - Chien-Ning Hsu; Chih-Yao Hou; Guo-Ping; Sufan Lin; You-Lin Tain (MDPI AG, 2020)
Hypertension can come from early life. N-acetylcysteine (NAC), a hydrogen sulfide (H2S) precursor as well as an antioxidant, has antihypertensive effect. We investigated whether maternal NAC therapy can protect spontaneously hypertensive rats (SHR) male offspring against hypertension. The pregnant rats were assigned to four groups: SHRs without treatment; Wistar Kyoto (WKY) without treatment; SHR+NAC, SHRs received 1% NAC in drinking water throughout pregnancy and lactation; and, WKY+NAC, WKY rats received 1% NAC in drinking water during pregnancy and lactation. Male offspring (n = 8/group) were killed at 12 weeks of age. Maternal NAC therapy prevented the rise in systolic blood pressure (BP) in male SHR offspring at 12 weeks of age. Renal cystathionine β-synthase (CBS) and 3-mercaptopyruvate sulphurtransferase (3MST) protein levels and H2S-releasing activity were increased in the SHR+NAC offspring. Maternal NAC therapy increased fecal H2S and thiosulfate levels in the SHR+NAC group. Additionally, maternal NAC therapy differentially shaped gut microbiota and caused a distinct enterotype in each group. The protective effect of maternal NAC therapy against hypertension in SHR offspring is related to increased phylum Actinobacteria and genera Bifidobacterium and Allobaculum, but decreased phylum Verrucomicrobia, genera Turicibacter, and Akkermansia. Several microbes were identified as microbial markers, including genera Bifidobacterium, Allobaculum, Holdemania, and Turicibacter. Our results indicated that antioxidant therapy by NAC in pregnant SHRs can prevent the developmental programming of hypertension in male adult offspring. Our findings highlight the interrelationships among H2S-generating pathway in the kidneys and gut, gut microbiota, and hypertension. The implications of maternal NAC therapy elicited long-term protective effects on hypertension in later life that still await further clinical translation.